Examining situated design practices: Nurses' transformations towards genuine participation. (November 2018) - Østergaard, Kija Lin; Simonsen, Jesper; Karasti, Helena
Abstract : We scrutinise the concrete practices of participants' engagement in participatory design through an empirical case in which nurses from different hospital wards began as reluctant users, but gradually engaged in processes approaching genuine participation. We expand a newly proposed, psychologically inspired perspective into a conceptual frame to investigate transformations towards genuine participation. This analytical lens elucidates how participants engage in becoming authentic, credible, attentive and present in participatory endeavours, and how this affects reflection and learning. The case includes the designer's process of becoming a genuine participant during the project. By offering a new take on the concept of genuine participation using a dimension characterised by a genuine, focused presence, we offer our lessons learnt from applying the framework. Highlights: An investigation of situated design practice and transformations towards genuine participation. A conceptual framework that emphasises quality in communication between participants. Participation and interpersonal dynamics as part of unfolding practices. The designer's process of becoming a genuine participant and being in-between roles. Reflective practice in situated design practices.